História oral: re-construindo a realidade e as relações sociais - NASCIMENTO, Ana Lídia Cardoso do (Universidade Federal do Pará, 2020)
The work to be presented is the result of the dissertation submitted in the curse of International Master in Planning of Development, in the Center for Advanced Amazonic Studies (NAEA), at the Federal University of Pará (UFPA), titled “Schools- family farms and the agricultural extractive activities in the state of Amapá: practices and meanings “, under the guidance of profª Drª. Ligia T. L. Simonian, defended in March 2005. The study aimed to carry out study on the experiences of the Schools-Familys in the state of Amapá, from the perspective of perceiving them as an alternative to education in rural areas with the potential to contribute to rural development in the state. The discussions for the construction proposal of these schools originate in the struggles by farmers, based on an analysis of their reality found that conventional rural schools did not meet their interests and that the pedagogical proposal for EFA could be a solution for education in rural areas. The article intends to present some issues noted during the development of the research in relation to the acquisition of knowledge through orality, guaranteeing the historical, cultural, social and economic rescue in a contexts of a given historical moment.